Use of LDH and autoimmune side effects to predict response to ipilimumab treatment - Dick, Julika; Lang, Nina; Schulz, Christof; Enk, Alexander; Hassel, Jessica C. (Immunotherapy, 2016)
Background: Ipilimumab is a cytotoxic T-lymphocyte antigen-4 antibody that enhances T-cell activity and proliferation. Methods: In a retrospective analysis of 86 patients the clinical benefits of ipilimumab treatment were correlated with laboratory and clinical data. Results: A lactate dehydrogenase (LDH) value within the normal range before the start of therapy was significantly correlated with better OS (p ≤ 0.009). An increase in LDH level after two cycles was indicative of a poor outcome, and was significantly negatively correlated with treatment response and overall survival and progression-free survival. 42% of all patients suffered from autoimmune toxicity (CTCAE grades 2-4). The occurrence of autoimmune toxicity clearly correlated with clinical benefit. Conclusion: Changes in LDH level and side effects correlate with response to therapy and survival.